THE COMMUNICATIVE COMPETENCE OF FUTURE TEACHERS - Pakhomova Irina Yurevna (Sovremennye Issledovaniâ Socialʹnyh Problem, 2013)
This article describes the concept of "communicative competence of future teachers," describes the essential characteristics and features of pedagogical communication. Objective: To define the notion of "communicative competence of future teachers' Methodology of work: competence approach. Scope of the results: the preparation of future teachers at the Pedagogical University. Results: This article describes the concept of "communicative competence of future teachers," describes the essential characteristics and features of pedagogical communication.